Socioeconomic status in the association between use of personal care products and exposure to endocrine-disrupting chemicals in pregnant Taiwanese women - Waits, Alexander; Chang, Chia-Huang; Huang, Yu-Fang; Tsai, Ming-Song; Hou, Jia-Woei; Wang, Pei-Wei; Chen, Chih-Yao; Hsieh, Chia-Jung; Wu, Ming-Tsang; Wang, Shu-Li; Chen, Mei-Lien (Frontiers in Public Health, 2025)
BackgroundMaternal exposure to endocrine-disrupting chemicals (EDCs), particularly those found in personal care products (PCPs), may affect child development. Socioeconomic inequalities in EDC exposure warrant further investigation. This study assessed the role of income and education in the association between PCP use and exposure to bisphenol A (BPA) and parabens in pregnant women.MethodsAssociations between PCP use and urinary concentrations of BPA and four parabens in pregnant women from the Taiwan Maternal and Infant Cohort Study were estimated using linear regression, with results expressed as the percentage change in concentrations for each additional PCP use per week. The analysis was stratified by income and education and predicted concentrations, and a 95% confidence interval (CI) was graphed according to the frequency of PCP use.ResultsHigher concentrations of methylparaben, ethylparaben, and propylparaben were associated with more frequent use of different PCPs, especially makeup. The above-lowest income group showed positive associations between frequency use of rinse-off PCPs and methylparaben (2.5%, 95%CI = 0.9%, 4.0%), propylparaben (2.8%, 95%CI = 0.3%, 5.3%), and between leave-on PCPs and methylparaben (3.1%, 95%CI = 1.8%, 4.4%), ethylparaben (2.2%, 95%CI = 0.1%, 4.2%), and propylparaben (2.8%, 95%CI = 0.8%, 4.9%). BPA was negatively associated with rinse-off PCPs (−1.2%, 95%CI = −2.3%, −0.2%). A positive association between leave-on PCPs and BPA was suggested in the lowest income group (1.7%, 95%CI = −0.4%, 3.7%). Predicted BPA concentrations were significantly higher in the lowest income group at higher frequencies of PCP use. Stratification by education showed the strongest associations in the postgraduate group for rinse-off PCPs with methylparaben (6.1%, 95%CI = 1.9%, 10.5%) and propylparaben (6.9%, 95%CI = 1.2%, 12.9%), as well as for leave-on PCPs with methylparaben (4.1%, 95%CI = 1.2%, 7.2%).ConclusionThe associations observed between various PCPs and parabens suggest that reducing the use of certain PCPs in pregnant women could help lower paraben exposure. Higher levels of BPA in the lowest income group require further investigation of sources of BPA exposure, especially in disadvantaged populations.